2011
DOI: 10.1093/rpd/ncr202
|View full text |Cite
|
Sign up to set email alerts
|

Dose conversion coefficients for neutron exposure to the lens of the human eye

Abstract: Dose conversion coefficients for the lens of the human eye have been calculated for neutron exposure at energies from 1 × 10(-9) to 20 MeV and several standard orientations: anterior-to-posterior, rotational and right lateral. MCNPX version 2.6.0, a Monte Carlo-based particle transport package, was used to determine the energy deposited in the lens of the eye. The human eyeball model was updated by partitioning the lens into sensitive and insensitive volumes as the anterior portion (sensitive volume) of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 4 publications
7
41
0
Order By: Relevance
“…Several scientific groups investigated the dose values for the lens for electrons (Behrens et al 2009;Behrens 2013;Nogueira et al 2011), photons (Behrens and Dietze 2010), and neutrons (Manger et al 2012) in different irradiation scenarios. In CT examinations, the absorbed dose was calculated for a simple eyeball modeled in a stylized phantom (Akhlaghi et al 2015c), for eye, cornea, and lenses in a stylized head phantom , and also for eye bulb and lens using voxel phantoms (Akhlaghi et al 2015b;Lee et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scientific groups investigated the dose values for the lens for electrons (Behrens et al 2009;Behrens 2013;Nogueira et al 2011), photons (Behrens and Dietze 2010), and neutrons (Manger et al 2012) in different irradiation scenarios. In CT examinations, the absorbed dose was calculated for a simple eyeball modeled in a stylized phantom (Akhlaghi et al 2015c), for eye, cornea, and lenses in a stylized head phantom , and also for eye bulb and lens using voxel phantoms (Akhlaghi et al 2015b;Lee et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Till now, these models have been widely used for calculation of dose conversion coefficients of the eye lens (Behrens et al 2009;Behrens and Dietze 2010;Nogueira et al 2011;Manger et al 2012;Sakhaee et al 2015;Vejdani-Noghreiyan and EbrahimiKhankook 2016). One of the most detailed models is the one designed by Nogueira and co-workers, in which lens cells were divided into sensitive and insensitive, and GZ was considered as the sensitive zone to ionizing radiation (Nogueira et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Solid curves give the final values of ICRP reference conversion coefficients for external neutrons as a function of neutron energy. Manger et al (2012) concluded that the dose to the sensitive region of the lens of the eye was similar to that of the total lens over all neutron energies and exposure geometries, with the greatest differences being 13% at the lowest incident neutron energy. Regardless of the orientation of the exposure, no significant difference was found in the absorbed dose in the sensitive volume and total volume of the lens of the eye.…”
Section: Electron Irradiation Of the Eyementioning
confidence: 99%
“…Geometric eye model of Manger et al (2012) for neutron dosimetry In 2012, the previous studies of electron and photon eye dosimetry were further extended to neutron ocular exposures. In a study by Manger et al (2012), the stylised eye model of Behrens et al (2009) was again adopted and inserted into a larger model of the head and neck. In this study, the latter model selected was that of the modified Oak Ridge National Laboratory stylised phantom as reported by Han et al (2006).…”
Section: Geometric Eye Model Of Behrens and Dietze (2011) For Photon mentioning
confidence: 99%
“…In this study, a modified Oak Ridge National Laboratory (ORNL) adult phantom (Miri Hakimabad et al, 2012) that included revisions reported in 1996 (Eckerman et al, 1996) and a thyroid model provided by Ulanovsky (Ulanovsky and Eckerman, 1998) were used. This latter phantom is the revised version of the Medical Internal Radiation Dose (MIRD) phantoms that have been widely used Lee et al, 2007;Manger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%